The Role Of The Indonesian Automatic Finger Print Identification System (Inafis) In Identifyng Perpetrators Of Murder Cases (A Cases Study In The Regional Police Of West Sumatera) - Yoga Pratama Pratama; Deaf Wahyuni Ramadhani (Activa Yuris: Jurnal Hukum, 2021)
Indonesia Automatic Finger Print Identification System (Inafis) is a unit that plays a role in identifying a person through scientific means, by examining fingerprints at a crime scene. As stipulated in Article 15 paragraph (1), Law Number 2 of 2002 concerning the Indonesian National Police states that, "taking the first action at a crime scene, taking fingerprints and identities and other photographs, seeking information and evidence, receiving and keeping findings for a while ". Indonesia Automatic Finger Print Identification System (Inafis) is a unit that plays a role in identifying a person through scientific means, by examining fingerprints at a crime scene. The police, especially the Inafis unit itself, are looking for fingerprints in the vicinity of the crime scene (TKP) which will later assist investigators in finding and arresting the perpetrators of the murder. The problems raised in this study are, How are the roles and constraints of the Indonesian Automatic Finger Print Identification System (Inafis) of the West Sumatra Regional Police in uncovering the perpetrators of murder